Fostering innovation competencies in tourism higher education via design-based and value-based learning. (November 2021) - Phi, Giang Thi; Clausen, Helene Balslev
Abstract: There is growing imperative for the development of innovation competencies to address both economic and social/environmental issues in the travel sector, within the context of sustainable development and the fourth industrial revolution. This paper explores a unique combination of design-based and value-based learning to foster students' innovation competencies, utilising a case study involving 60 Master of Tourism students in 'Innovation in Tourism' course. Results suggest that the combined pedagogies are effective in fostering creative problem-solving, system thinking, goal orientation, teamwork and networking. However higher education institutions need to better adapt both the administration and the curriculum to accommodate different tasks and teaching roles.